ANALYSIS FACTOR OF LOW BIRTH WEIGHT INCIDENCE IN RSUD GAMBIRAN KOTA KEDIRI - Anna Nurhidayati; Melda Byba Suhita; Indasah Indasah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2017)
Determinants of children in health status of community health status was infant mortality rate (IMR), One of the causes of infant mortality are low birth weight (LBW) 8 times greater than normal babies. The objective of this research was to analyze the effects of age, stress, parity, nutritional status, and anemia experienced by the mother during pregnancy that affect the incidence of low birth weight in RSUD Gambiran Kota Kediri. The design of this research was observational study design with cross Sectional (cross sectional study). This research was conducted on the 29th of July until 2nd of October 2017 in RSUD Gambiran Kota Kediri. The sample size of this study was 88 mothers of babies with low birth weight are treated in RSUD Gambiran Kota Kediri. The independent variables were age, stress, parity, nutritional status, and anemia experienced by the mother during pregnancy. The dependent variable was low birth weight. Data analysis using regression logistic multinomial with the results of the study showed age (p-value = 0.001), stress levels (p-value = 0.439), parity (p-value = 0.326), nutritional status (p-value = 0.322), anemia gravidarum (p-value 0.019). The results showed that the age of the mother during pregnancy and anemia gravidarum was significant effect on the incidence of low birth weight. Moderate levels of stress, parity, and nutritional status have no significant influence on the incidence of low birth weight in RSUD Gambiran Kota Kediri.